Aromatase inhibitors in the treatment of oligozoospermic or azoospermic men: A systematic review of randomized controlled trials - Ribeiro, Mariana Antunes [UNESP]; Gameiro, Luís F. O. [UNESP]; Scarano, Wellerson R. [UNESP]; Briton-Jones, Christine; Kapoor, Anil; Rosa, Mauro B.; El Dib, Regina [UNESP] (GN1 Sistemas e Publicacoes, 2016)
The aim of this study as to analyze published evidence regarding the effectiveness of aromatase inhibitor therapy on improving spermatogenesis in infertile men. We carried out a systematic review of randomized controlled trials. The date of the most recent search was October 4, 2015. Two authors independently selected relevant clinical trials, assessing their methodological quality and extracting data. Three studies were included in this review with a total of 100 participants; however, we were able to include data from only 54 participants in the analysis. In the representation of meta-analysis with a single study comparing testolactone versus placebo, related to the hormone concentrations, there was a statistically significance difference favoring the use of testolactone for Luteinizing Hormone (LH); Estrogen (E2); free Testosterone (free T); free Estrogen (free E2); 17-Hydroxyprogesterone (17OHP); prolactin (PRL). In another analysis from a single study comparing letrozole versus anastrozole, there was also a statistically significance difference favoring the use of letrozole for the increase in both the sperm count and LH. There is only low quality evidence regarding the effectiveness of aromatase inhibitor therapy in infertile men. Further trials are needed with standardized interventions and outcomes.
Keywords: Aromatase inhibitors; Infertile men; Meta-analysis; Spermatogenesis